The Rationality of Gis Fm Radio Fans Amid the Rise of Social Media - Arifah Roselina Irawati; Okta Hadi Nurcahyono; Yuhastina Yuhastina (LPPM Universitas PGRI Sumatera Barat, 2021)
At this time, various social media have emerged which function like radio. The convenience provided by social media made people use it. So that social media users were increasing and it was possible to reduce radio fans. But on the one hand, there were still people who like radio broadcasts. This study aimed to explain the reasons why fans are still listening to GIS FM radio amid social media. This research used qualitative research methods with data collection techniques interview, observation, and documentation. The validity of the data used technical triangulation. The results of this study indicate that fans are still loyal to listen to GIS FM radio broadcasts. The rationality of fan action was seen in the tradition of sending attention depicts traditional rationality, the enjoyment arising from reading attention by broadcasters that depict affective rationality, the effectiveness of radio as a tool that is easily controlled illustrates instrumental rationality, and the closeness that fans and broadcasters build represent value-oriented rationality. This made fans still listen to GIS FM radio amid the rise of social media.